(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This study analyzes the predictive validity of the 2025 Tryout Examination items for the Teacher Professional Education Competency Test (UKPPPG) in History, developed by the Universitas Negeri Malang PPG team. The study aims to ensure the quality of evaluation instruments and assess their ability to predict participants’ success in the official competency test. Employing a mixed-methods explanatory sequential design, quantitative analysis was conducted to evaluate item validity, reliability, difficulty, and discrimination indices using data from 45 PPG-BGT History participants, followed by qualitative interviews with three purposively selected respondents. Results indicate that while some items exhibited weaknesses in psychometric properties, the tryout was perceived as effective in helping participants understand the structure, content, and cognitive demands of the UKPPPG. The findings confirm the value of integrating psychometric evaluation with user perception analysis for improving test instrument accuracy. This study contributes theoretically to the refinement of teacher assessment standards and practically provides recommendations for enhancing item construction and predictive performance in professional teacher education.